Comparison of Polyphenol-Enriched Tomato Juice and Standard Tomato Juice for Cardiovascular Benefits in Subjects with Stage 1 Hypertension: a Randomized Controlled Study - Michaličková, Danica; Belović, Miona; Ilić, Nebojša; Kotur-Stevuljević, Jelena; Slanař, Ondřej; Šobajić, Sladjana (Plant foods for human nutrition (Dordrecht, Netherlands), 2019)
There is a growing body of evidence that tomato consumption reduces the risk of cardiovascular disease, through antioxidative, anti-inflammatory and hypotensive effects. We compared the effects of polyphenol-enriched and standard tomato juice on parameters of lipid and oxidative status and blood pressure in subjects with stage 1 hypertension. The experimental group (n = 13) was supplemented with 200 g of tomato fruit juice enriched with 1 g of ethanolic extract of whole tomato fruit, while the control group (n = 13) was consuming 200 g tomato fruit juice. Before and after the treatment, blood samples were collected, and blood pressure was measured. Markers of oxidative stress and antioxidative defense: paraoxonase (PON1), thiobarbituric acid reactive substances (TBARS), total antioxidant status (TAS), total oxidant status (TOS), pro-oxidant-antioxidant balance (PAB) and C reactive protein (CRP) were determined in serum. Prothrombin time (PT) was measured in the whole blood samples. Parameters of lipid status, as well as susceptibility to copper-induced oxidation of LDL particles in vitro were also determined. There was a significant reduction in total cholesterol and LDL-C only in the control group at the end of the study. No significant differences were observed in the remainder of the assessed parameters along the study. In conclusion, tomato juice may have favorable effects on lipid metabolism, but polyphenol fortification does not constitute additional beneficial cardiovascular effects.
Keywords: hypertenze; Antioxidants; jednoduchá slepá metoda; Female; Cardiovascular risk; biologické markery; oxidační stres; Biomarkers; Fruit and Vegetable Juices; ovocné a zeleninové šťávy; ženské pohlaví; Polyphenols; Dietary Supplements; lipidy; Oxidative Stress; lidé; potravní doplňky; Lipids; krevní tlak; Single-Blind Method; Human intervention studies; Humans; Hypertension; Male; Cardiovascular Diseases; antioxidancia; kardiovaskulární nemoci; polyfenoly; lidé středního věku; mužské pohlaví; Blood Pressure; Middle Aged; Solanum lycopersicum